The vicious cycle of chronic endometriosis and depression—an immunological and physiological perspective - Sherwani, Subuhi; Khan, Mohd Wajid Ali; Rajendrasozhan, Saravanan; Al-Motair, Khalid; Husain, Qayyum; Khan, Wahid Ali (Frontiers in Medicine, 2024)
Endometriosis is a chronic, estrogen-dependent, proinflammatory disease that can cause various dysfunctions. The main clinical manifestations of endometriosis include chronic pelvic pain and impaired fertility. The disease is characterized by a spectrum of dysfunctions spanning hormonal signaling, inflammation, immune dysregulation, angiogenesis, neurogenic inflammation, epigenetic alterations, and tissue remodeling. Dysregulated hormonal signaling, particularly involving estrogen and progesterone, drives abnormal growth and survival of endometrial-like tissue outside the uterus. Chronic inflammation, marked by immune cell infiltration and inflammatory mediator secretion, perpetuates tissue damage and pain. Altered immune function, impaired ectopic tissue clearance, and dysregulated cytokine production contribute to immune dysregulation. Enhanced angiogenesis promotes lesion growth and survival. Epigenetic modifications influence gene expression patterns, e.g., HSD11B1 gene, affecting disease pathogenesis. Endometriosis related changes and infertility lead to depression in diagnosed women. Depression changes lifestyle and induces physiological and immunological changes. A higher rate of depression and anxiety has been reported in women diagnosed with endometriosis, unleashing physiological, clinical and immune imbalances which further accelerate chronic endometriosis or vice versa. Thus, both endometriosis and depression are concomitantly part of a vicious cycle that enhance disease complications. A multidimensional treatment strategy is needed which can cater for both endometrial disease and depression and anxiety disorders.